Unravelling the synergistic effects in GdCe composite oxides supported biochar catalysts for formaldehyde elimination: Elevated performance and SO2 toleration - Jiang, Yun; Gao, Lei; Dai, Jianyong; Li, Caiting; Xiong, Huiyu; Li, Yeling; Liu, Zhichao; Wang, Wenjun; Hu, Junhao (Journal of environmental sciences (China), 2025)
•GdCe bimetallic catalyst exhibited superior performance and SO2 toleration than those of corresponding monometallic catalyst.•The synergistic effect between GdOx and CeOx in 10%Gd0.25Ce0.75/MPB boosted oxygen vacancies formation and active oxygen evolution.•Effects of flue gas components were explored to fulfill the industrial application.•A possible mechanism for HCHO abatement over 10%Gd0.25Ce0.75/MPB was proposed by In-situ DRIFTS. A chain of GdCe oxides boosted biochars derived from maize straw and sewage sludge (GdyCe1-y/MPBs) were fabricated for formaldehyde (HCHO) catalytic decomposition. The ingenerate relationship between the abatement performance and corresponding structural feature was comprehensively evaluated by XPS, in situ DRIFTS, BET, XRD, SEM and H2-TPR. Meanwhile, 10%Gd0.25Ce0.75/MPB exhibited excellent performance, favorable SO2 and moisture toleration over a broad temperature range from 160 to 320 ℃, where it achieved 96.8% removal efficiency with 90.5% selectivity at 200 ℃. The single or united effects of O2, SO2, H2O on HCHO abatement over 10%Gd0.25Ce0.75/MPB were tested, and the findings demonstrated that the suppressive effects of SO2 and H2O outweighed the promoting influence of O2 within a specific range. Gd and Ce co-modified MPB revealed superior HCHO removal capability in contrast to that of Gd or Ce severally modified MPB, ascribing to the synergistic effect of GdOx and CeOx and benefitting from the augmentation of surface area and total pore volume, the aggrandizement of surface active oxygen species, the promotion of redox ability and the inhibition crystallization of CeOx. According to in situ DRIFTS, a series of intermediates including formate species and dioxymethylene (DOM) were produced, which would eventually decompose into H2O and CO2. In addition, the mass transfer and diffusion of the reactants along with the accessibility of the catalytic sites were enlarged by the hierarchical porous structure of the support, which were also answerable for its distinguished catalytic performance. Furthermore, 10%Gd0.25Ce0.75/MPB possessed remarkable potential for industrial applications. [Display omitted]